Practical image and video processing using MATLAB - Marques, Oge. (New Jersey : Wiley, 2011)
"The book provides a practical introduction to the most important topics in image and video processing using MATLAB (and its Image Processing Toolbox) as a tool to demonstrate the most important techniques and algorithms. The contents are presented in a clear, technically accurate, objective way, with just enough mathematical detail. Most of the chapters are supported by figures, examples, illustrative problems, MATLAB scripts, suggestions for further reading, bibliographical references, useful Web sites, and exercises and computer projects to extend the understanding of their contents"--Provided by publisher.
Includes bibliographical references and index.
Keywords: MATLAB; Image processing -- Mathematics; Image processing -- Digital techniques; Digital video -- Mathematics